"But Before I Go to My Next Step": A Longitudinal Study of Adolescent English Language Learners' Transitional Devices in Oral Presentations. Issue 2 (15th April 2013) - Kibler, Amanda K.; Salerno, April S.; Palacios, Natalia
Abstract : This multiple case study examines patterns in the oral second language use of three Spanish‐speaking English language learners in rehearsed presentations produced annually over 4 years (Grades 9–12) in a U.S. high school. Analysis focuses on students' changing use of transitional devices called frame markers (Hyland, 2005) as a lens for understanding language used by school‐aged immigrant students in academic settings, the nature of classroom presentations, and the role of a range of contextual factors from a longitudinal perspective. Students produced relatively complex structures to mark transitions, even at early proficiency levels, likely due to opportunities for rehearsal and use of supporting written texts. Despite notable commonalities, students took varied paths in language use, responding individually to presentational environments. Such findings provide evidence that both context and individual variation contribute to oral second language use in school settings and provide a rationale for research that attends to academic and presentational settings in which students produce oral language.